Design and experimental study of a rotational piezoelectric energy harvester. (1st October 2022) - Farias, W.P.; Souto, C.R.; Castro, A.C.
Abstract: This article presents the characterization of an rotational generator with ceramic piezoelectric transducers, applied to energy harvesting. The physical structure developed, presents flexibility in relation to the number of beams, piezoelectric elements and coupling of generator modules, and keeps the piezoelectric transducers without direct contact with extern environment, which allows the device adaptation for practical applications. The prototype developed has two generator modules, totaling four beams with two piezoelectric transducers PZT C-64 each, and it worked for approximately 670 hours, without waste signs. An experimental configuration was developed to analyze the behavior of the proposed generator, with the generator being driven by a motor coupled to its axis with a rotation speed of 1 Hz to 35 Hz. The signals generated by the beans were connected to variable resistors, obtaining different power values in each one of the blades, justified by the manual manufacturing process. The results showed that the suggested harvester has high durability and the potential to power wireless sensors that are integrated into rotating machines.